PENGARUH DEBT TO EQUITY RATIO (DER), TOTAL ASSET TURNOVER (TATO), DAN NET PROFIT MARGIN (NPM) TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016 - 2020 - Yolanda Manurung Yolanda Manurung; Arifin Siagian (Jurnal Manajemen, 2023)
Every company has a goal to gain profit growth in its business. This research was conducted to examine the effect of Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Net Profit Margin (NPM) on Profit Growth partially or simultaneously with data collection methods using secondary data in the form of financial reports on food and beverage companies listed on the Indonesia Stock Exchange. The population in this study were 33 food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sample in this study were 13 companies using purposive sampling technique. The analytical methods used in this research are Descriptive Statistical Analysis, Coefficient of Determination Analysis, and Multiple Linear Analysis. The results of this study indicate that simultaneously Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Net Profit Margin (NPM) have an effect on Profit Growth. Partially Debt To Equity Ratio (DER) has an effect on profit growth, Total Asset Turnover (TATO) has no effect on profit growth, and Net Profit Margin (NPM) has an effect on profit growth